РАЗВИТИЕ СЕТИ ПУЩИНСКОГО НАУЧНОГО ЦЕНТРА - Исаев, Е. А.; Пугачев, В. Д.; Думский, Д. В.; Зайцев, А. Ю.; Самодуров, В. А.; Беляцкий, Ю. А.; Бородаенко, С. Б.; Лихачев, С. Ф.; Шацкая, М. В.; Корнилов, В. В.; Китаева, М. А.; Овчинников, И. Л.; et al. (Одеські астрономічні публікації, 2011)
Development of fundamental science today depends largely on the availability of modern computing and communications resources. Pushchino Research Center consists of 8 institutes and 2 branches of RAS, including specialized research facilities and system of data processing and storage, as well as a number of other objects. And all these objects combined into a single local area network built on fiber optical channels and on the signal topology named "star". The main management servers that organize routing and provide the necessary Internet services (mail, web servers, databases, etc.) are located in the center of the network at the Institute of Mathematical Problems of Biology. Servers work under control of virtualization system. The network of Pushchino Research Center includes a high-performance cluster with total performance about 830 gigaflops, designed for resource-intensive computing tasks of broad range basic research. A separate external optical communication channel with data rate 1 Gbit/s created in the Pushchino Radio Astronomy Observatory in the framework of international project of space radio telescope "Radioastron" together with the company «Stack Group».